2020
DOI: 10.7759/cureus.7848
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease in Children: Experience and Constraints in a Resource-limited Setting

Abstract: Introduction: Inflammatory bowel disease (IBD), though well described in the Caucasian population, is rarely encountered in the black African children. The aim of this study was to increase the awareness of this emerging condition in African children and highlight the constraints of management in a resourcelimited setting like Nigeria.Methods: This study included an audit of children with IBD who were seen between January 2015 and February 2020 at the Lagos University Teaching Hospital (LUTH). The clinical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Following recent initiatives to raise awareness of IBD in SSA a number of case series and cohort studies have been published which have added to the numbers identified in the aforementioned systematic reviews, suggesting that the incidence of IBD in the subcontinent is likely on the increase. 27,31–34,82,83…”
Section: Measures Underway To Improve Ibd Diagnostic Capacity and Med...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following recent initiatives to raise awareness of IBD in SSA a number of case series and cohort studies have been published which have added to the numbers identified in the aforementioned systematic reviews, suggesting that the incidence of IBD in the subcontinent is likely on the increase. 27,31–34,82,83…”
Section: Measures Underway To Improve Ibd Diagnostic Capacity and Med...mentioning
confidence: 99%
“…81 Following recent initiatives to raise awareness of IBD in SSA a number of case series and cohort studies have been published which have added to the numbers identified in the aforementioned systematic reviews, suggesting that the incidence of IBD in the subcontinent is likely on the increase. 27,[31][32][33][34]82,83 While comprehensive epidemiological data are lacking, there are many plausible environmental explanations for this observation, such as changes in diet from the traditional African diet rich in fibre, fruit and vegetables, to a more westernized diet high in sugar, saturated fat, emulsifiers and preservatives which appear to increase the risk of developing IBD. 6 In addition, the widespread eradication of Helminth infections, Schistosomiasis and Helicobacter pylori, which may confer a protective effect, could have contributed to an increase in cases in SSA.…”
Section: Histopathology Services In Ssamentioning
confidence: 99%
“…Other gastrointestinal disorders, such as coeliac disease and inflammatory bowel disease, were previously thought to be non‐existent or rare in sub‐Saharan Africa. However, they are increasingly being recorded in some of these African countries due to greater awareness and improved diagnostic capability 4–7 . Accurate diagnosis and effective treatment for some of these disorders require special skills, which may not be available without trained paediatric gastroenterologists 1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, they are increasingly being recorded in some of these African countries due to greater awareness and improved diagnostic capability. [4][5][6][7] Accurate diagnosis and effective treatment for some of these disorders require special skills, which may not be available without trained paediatric gastroenterologists. 1 Paediatric gastroenterology is in its infancy in Africa, but South Africa and Egypt have the edge over other countries.…”
mentioning
confidence: 99%